Debt and Subjective Well-Being: Does the Type of Debt Matter? - Coste Tristan; Henchoz Caroline; Wernli Boris (Swiss Journal of Sociology)
Based on longitudinal analyses of data from the Swiss Household Panel, this paper investigates the effect of different types of debt on two evaluative measures of subjective well-being: financial satisfaction and life satisfaction. Payment arrears reduce financial satisfaction more than loans or the accumulation of different types of debt (arrears and loans). This negative effect is stable over time. Conversely, each additional year with arrears decreases life satisfaction, confirming the overall and general negative effect of arrears on all domains of daily life, especially for the elderly.